Infectious complications in lupus nephritis treatment: a systematic review and meta-analysis. (March 2019) - Thong, K M; Chan, T M
Objectives: Infection is an important concern in lupus nephritis treatment, but few studies have focused on this complication. Available data suggest marked variation in occurrence and outcome. This meta-analysis and review aims to provide an overview of infective complications, focusing on the risk factors and outcomes. Methods: Original articles on lupus nephritis Class III/IV/V published in the period January 1980 to December 2016 were identified from the Pubmed/Medline electronic database. Meta-analysis of randomized controlled trials was performed to investigate total and serious infections at different phases of treatment and their associated factors. A descriptive review that included all studies was also performed, providing details on the types of infection, infection-related mortality, and potential impact of different eras on infection rates. Results: A total of 56 studies (32 randomized controlled trials) were included. The incidence rates of overall and serious infections were higher during the induction than maintenance phase of therapy, with serious infections occurring at 8.2–50 and 3.5 per 100 patient-years, respectively. Recent data, predominantly from Asia, suggested lower rates of overall infections with induction regimens that included tacrolimus compared with mycophenolate (risk ratio 0.50, 95% confidence interval 0.33–0.76, p = 0.001). Mycophenolate as induction treatment was associated with lower overall infection risks than cyclophosphamide in non-Asians (risk ratio 0.60, 95% confidence interval 0.48–0.75, p < 0.001). The rates of serious infections were 4.1–25% in Asian and 4.4–8.5% in non-Asian countries; with infection-related mortality rates of 0–6.7% in Asian, compared to 0–2.1% in non-Asian locations. Conclusions: Infection remains a serious complication during treatment of lupus nephritis, but the reported rates and outcomes varied markedly. Mycophenolate was associated with lower infection risk than cyclophosphamide in non-Asians. Infection-related deaths appeared more common in Asian patients.